Multilevel Analysis on the Effect of Marketing Mix Strategy toward Patient Satisfaction in Magelang, Central Java - Lu’luatul Fuad; Didik Tamtomo; Endang Sutisna Sulaeman (Masters Program in Public Health, Sebelas Maret University, 2019)
Background: Hospital marketing is becoming increasingly competitive all over the world. The marketing mix strategy is considered one of the core concepts of marketing theory. This study aimed to examine the effect of marketing mix strategy toward patient satisfaction in Magelang, Central Java.Subjects and Method: A cross sectional study was conducted at Magelang Hospital, Central Java, in December 2018. A sample of 200 patients was selected by simple random sampling. The dependent variable was patient satisfaction. The independent variables were product, price, place, promotion, process, people, physical appearance, and ward. The data were collected by questionnaire and analyzed by multilevel multiple logistic regression.Results: Patient satisfaction increased with good product (b= 3.42; 95% CI= 0.76 to 2.81; p<0.001), low price (b= 1.92; 95% CI= -0.05 to 1.70; p= 0.054), right place (b= 2.41; 95% CI= 0.19 to 1.92; p= 0.016), attractive promotion (b= 2.92; 95% CI= 0.43 to 2.19; p= 0.004), people (b= 1.91; 95% CI= -0.24 to 1.75; p= 0.057), good physical appearance (b= 2.42; 95% CI= 0.20 to 1.97; p= 0.015), and sound process (b= 2.07; 95% CI= 0.45 to 1.72; p= 0.039). Ward had a considerable contextual effect on patient satisfaction with ICC= 14.65%.Conclusion: Patient satisfaction increases with good product, low price, right place, attractive promotion, people, good physical appearance, and sound process. Ward has a considerable contextual effect on patient satisfaction.Keywords: marketing mix, patient satisfaction, hospital, multilevel analysisCorrespondence: Lu’luatul Fuad. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: afuadlulu@gmail.com. Mobile: +6285643702066.Journal of Health Policy and Management (2019), 4(1): 39-46https://doi.org/10.26911/thejhpm.2019.04.01.05